Learning during motherhood: A resistance to stress - Leuner, Benedetta (2006)
Hormonal and emotional responses to stress are diminished during pregnancy and the postpartum period. However, the effects of stress on learning during these stages of the female life span have not been examined. In previous studies, we have reported that exposure to an acute stressful event reduces classical eyeblink conditioning 24 h later in adult virgin female rats that are experiencing an ovarian cycle. Here we show that conditioning during late pregnancy was similarly reduced by stressful experience. However, conditioning in postpartum females was unaffected by stressor exposure. The resistance to stress during the postpartum period was evident as early as 2 days after parturition and persisted until the late postpartum period, just prior to weaning. Postpartum conditioning was unresponsive to numerous types of stressors, including brief inescapable tailshocks, swim stress, and exposure to a male intruder. The resistance to stress appears to be dependent on the presence of the offspring, because the impairment in conditioning returned when postpartum females were separated from their pups. Moreover, the resistance to stress occurred in virgin females that behaved maternally after being exposed to young pups for several days. Together, these data suggest that the presence of offspring and the nurturing and care-giving activities that they elicit protect females from the adverse effect of stress on processes involved in learning and memory.